The Substantia Nigra Pars Compacta and Temporal Processing - Jahanshahi, Marjan; Jones, Catherine R. G; Dirnberger, Georg; Frith, Christopher D (The Journal of neuroscience, 2006)
The basal ganglia and cerebellum are considered to play a role in timing, although their differential roles in timing remain unclear. It has been proposed that the timing of short milliseconds-range intervals involves the cerebellum, whereas longer seconds-range intervals engage the basal ganglia (Ivry, 1996). We tested this hypothesis using positron emission tomography to measure regional cerebral blood flow in eight right-handed males during estimation and reproduction of long and short intervals. Subjects performed three tasks: (1) reproduction of a short 500 ms interval, (2) reproduction of a long 2 s interval, and (3) a control simple reaction time (RT) task. We compared the two time reproduction tasks with the control RT task to investigate activity associated with temporal processing once additional cognitive, motor, or sensory processing was controlled. We found foci in the left substantia nigra and the left lateral premotor cortex to be significantly more activated in the time reproduction tasks than the control RT task. The left caudate nucleus and right cerebellum were more active in the short relative to the long interval, whereas greater activation of the right putamen and right cerebellum occurred in the long rather than the short interval. These results suggest that the basal ganglia and the cerebellum are engaged by reproduction of both long and short intervals but play different roles. The fundamental role of the substantia nigra in temporal processing is discussed in relation to previous animal lesion studies and evidence for the modulating influence of dopamine on temporal processing.